Vitamin C promotes the early reprogramming of fetal canine fibroblasts into induced pluripotent stem cells - Sang Eun Kim; Jun Sung Lee; Keon Bong Oh; https://orcid.or 0002-0651-0306 (The Korean Society of Animal Reproduction and Biotechnology, 2023)
Background: Canine induced pluripotent stem cells (iPSCs) are an attractive source for veterinary regenerative medicine, disease modeling, and drug development. Here we used vitamin C (Vc) to improve the reprogramming efficiency of canine iPSCs, and its functions in the reprogramming process were elucidated. Methods: Retroviral transduction of Oct4, Sox2, Klf4, c-Myc (OSKM), and GFP was employed to induce reprogramming in canine fetal fibroblasts. Following transduction, the culture medium was subsequently replaced with ESC medium containing Vc to determine the effect on reprogramming activity. Results: The number of AP-positive iPSC colonies dramatically increased in culture conditions supplemented with Vc. Vc enhanced the efficacy of retrovirus transduction, which appears to be correlated with enhanced cell proliferation capacity. To confirm the characteristics of the Vc-treated iPSCs, the cells were cultured to passage 5, and pluripotency markers including Oct4, Sox2, Nanog, and Tra-1-60 were observed by immunocytochemistry. The expression of endogenous pluripotent genes (Oct4, Nanog, Rex1, and telomerase) were also verified by PCR. The complete silencing of exogenously transduced human OSKM factors was observed exclusively in canine iPSCs treated with Vc. Canine iPSCs treated with Vc are capable of forming embryoid bodies in vitro and have spontaneously differentiated into three germ layers. Conclusions: Our findings emphasize a straightforward method for enhancing the efficiency of canine iPSC generation and provide insight into the Vc effect on the reprogramming process.